Новые данные о Березанском поселении классического периода - Чистов, Д.Е.; Ильина, Ю.И. (Археологія і давня історія України, 2015)
Статья посвящена публикации нового комплекса – многокамерной постройки середины –
второй половины V в. до н.э. из раскопок Березанского поселения. Десятиріччя археологічних досліджень у Північно-Західній частині острова Березань привело
до припущення, що у класичний період, починаючи з раннього п`ятого століття до нашої ери, поселення Березань у силу деяких зовнішніх причин
занепало. Це припущення було доведене на матеріалах недавніх розкопок у північно-східній частині ділянки. Там, на місці архаїчних громадських
споруд були виявлені декілька структур, що датуються серединою – другою половиною 5 ст. до н.е.
Серед останніх – землянки, схожі на класичні, що
були виявлені раніше у північно–західній частині,
господарські ями, а також багатокамерні будинки
з глинобитними стінами. Хоч залишки структур досить нечисленні, зафіксовано два підвали і невеликі залишки наземних споруд. Були виявлені також сирцові глинобитні структури. Decades of the archaeological explorations in the
North-Western part of the Berezan island resulted
in the suggestion that during the Classical period,
starting with the early 5th century BC, the Berezan
settlement slid into decline due to a number of the
external circumstances. This assumption was proved
by recent excavations in the north-eastern part of the
site. There, on the place of the former late Archaic
civic buildings, several structures dated to the middle
– second half of the 5th century BC were uncovered.
Among the latter – dugouts, similar to the classical
ones uncovered earlier in the north-western sections,
storage pits; and also the remains of the multi-chamber
house build of stone and mudbricks. Although the
preservation of the structure is quite poor, two cellars
and few remains of the surface mudbrick walls
were uncovered. It should be noted that this building
was erected right on the spot of the yard of the former
civic building, probably a hestiatorion, therefore, the
latter did not exist when the house was built. Finds of
ceramics, including the storage amphorae and tableware
and characteristic of the period, help to place
the timespan of the house from the middle of 5th century
BC and up to the end of the same century.